FINANCIAL PERFORMANCE IN WEST NUSA TENGGARA (Case Study Before and After The Covid Pandemic) - Fadlli, Muhammad Dzul; Hidayat, Ali Akbar; Hak, Muhamad Bai'ul; Jannah, Widyatul (Journal of Finance, Economics and Business, 2024)
The Covid-19 pandemic has affected the government's financial performance. This study aims to analyze the impact of the pandemic on the financial performance of local governments in West Nusa Tenggara before and after COVID-19. The financial performance studied is such as the regional independence ratio, the effectiveness ratio and the government expenditure efficiency ratio. This study will use a quantitative approach to determine the impact of the pandemic on financial performance. This study compares financial performance before and after Covid-19 as an indicator of the impact of the pandemic. The data analysis technique used was in the form of a differential test. The data used is in the form of secondary data from the Ministry of Finance in the form of Regional Revenue and Expenditure Budget (APBD) data for Regional Governments in NTB in 2017-2022. The regional independence ratio has no difference in the average before and after, while the effectiveness ratio and efficiency ratio have a difference in performance before and after covid-19 with better financial performance conditions before covid-19.